The visible librarian : asserting your value with marketing and advocacy - Siess, Judith A. (American Library Association, 2003)
Here are all the tools you need to make your community aware of just how indispensable your services are. Expert librarian Judith Siess offers practical strategies to connect with customers, make services both visible and valuable to the community, and get the word out using proven marketing, customer service and public relations tactics specifically tailored to the library environment. Packed with all the best practices in marketing library services, this hands-on guide provides inspiring stories and case studies of library colleagues around the nation who are successfully advocating and marketing themselves and their services.